THE EFFECT OF OKETANI MASSAGE ON BREAST MILK IN POST PARTUM MOTHER IN PMB DINCE SAFRINA - Mayasari, Windy; ., Yanti; ., Lailiyana (Poltekkes Kemenkes Riau Under Health Ministry Republik Indonesia, 2020)
Abstract Ministry of Health 2017 states that exclusive breastfeeding coverage in Riauin 2017 is 28.57% of the 80% national target. As many as 50% ofpostpartum mothers who experience breastfeeding problems, such as lowbreastfeeding on the first to the third day of birth. One way to expeditebreastfeeding is by using the oketani massage method. The purpose of thisstudy was to determine the effect of massage on breastfeeding in postpartum mothers. This type of research is a quantitative research using a quasiexperiment with a post test only design with a control group. This researchwas conducted from December 2018 to June 2019 at PMB Dince Safrina. Thepopulation in this study were all normal post partum mothers from March toMay 2019. The sample in this study was 30 post partum mothers taken bypurposive sampling. The data collection instrument in this study was theobservation sheet that was filled in by the researcher directly throughobservation, after doing oketani massage for 3 days. Methods of datacollection in this study, the intervention group performed oketani massage for3 days (1 time a day) with a duration of 5-10 minutes and immediatelyobserved it on the third day using observation sheets, and the control groupdid not do oketani massage. The statistical test used was the Mann Whitneytest. The results of this study showed that there was an effect of massagetreatment on breastfeeding in post partum mothers (p = 0.003). It is hopedthat oketani massage can be applied in PMB Dince Safrina as an alternativeto help speed up breastfeeding and prevent problems during breastfeedingin post partum mothers such as flat nipples and breast milk dams.